Open science as an approach to curbing invisible science in Africa: the case of the University of Lomé (Togo) - (:unkn) unknown (My University, 2024)
Global science is witnessing a movement to open up scientific research thanks to the opportunities offered by ICTs, with a view to establishing new operating rules for the editorial ecosystem of scientific communication. Faced with major challenges to its place in world science, African science finds other challenges in open science, given that its scientific output is isolated and invisible. This reality is highlighted by bibliometric data revealing that sub-Saharan Africa contributes only 1% of world output. While the transformation within the scientific communication ecosystem offers opportunities for openness, based on a 3-phase empirical study conducted at the University of Lomé (Togo) as part of a cotutelle thesis, this paper highlights the potential benefits of open science to overcome the invisibility of African science.
Keywords: African Research